Kajian Hukum Kualifkasi Sanksi Kebiri Kimia Sebagai Sanksi Tindakan dalam Hukum Pidana di Indonesia - Tantimin Tantimin (Universitas Batanghari Jambi, 2021)
Castration is an action given to perpetrators of sexual crimes against children, in addition to imprisonment and fines. The purpose of this article is to find out the basic differences between criminal sanctions and action sanctions, to know the position of castration as an action sanction in criminal law and to analyze the castration penalty does not apply to children as perpetrators of sexual crimes. This research uses doctrinal legal research. Sources of legal information use primary legal materials (regulations and relevant documents) for further qualitative analysis. The approach used is statutory, conceptual, and analysis to help solve the problem formulation. The results of the research show that, at first glance, criminal sanctions and sanctions are often vague to distinguish, but at the level of basic ideas, there are very clear differences between the two types of sanctions. The reactive nature of an act is contained in the criminal sanction which connotes giving an affliction, while the anticipatory nature of the perpetrator of the act is contained in the sanction of action which connotes giving a remedy. The position of castration in the criminal system in Indonesia is not a principal, additional or a burden, but includes a sanction of action. Actions in the form of chemical castration are exempted for child offenders.